VLOG AS ALTERNATIVE MEDIA IN TEACHING SPEAKING FOR MILLENIAL LEARNERS - Lukman Arsyad; Enni Akhmad; Faratika Al Bayan (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
The study of media in teaching has been shifting toward language teaching. However the state and the determinants of Vlog as a media in teaching remains under explored particularly in the context of English speaking skill for millennial learners. This study aims to find out the effectiveness of Vlog as a media in teaching toward the students’ speaking skill in university level. This study involved 15 (fifteen) respondents taken randomly from the population of 30 fifth year undergraduate students of the English Education Department in one Indonesian Islamic institution. Data were collected using valid and reliable test and questionnaires and were analyzed with SPSS 16. Before the regression tests prerequisite tests of normality and linearity were administered. This studyshowed that Vlog has high impact to boost the students’ speaking skill.Vlog was familiar for the millennial learners, it was easy to be used, and madethe students felt free in expressing their ideas. Consequently, to make the students have the competence in speaking, the lecturer should find out the familiar media in teaching. The millennial learners preferred audio visual media.